Nature-based solutions as discursive tools and contested practices in urban nature's neoliberalisation processes. (June 2021) - Kotsila, Panagiota; Anguelovski, Isabelle; Baró, Francesc; Langemeyer, Johannes; Sekulova, Filka; JT Connolly, James
'Nature-based solutions' is the new jargon used to promote ideas of urban sustainability, which is gaining traction in both academic and policy circles, especially in the European Union. Through an analysis of the definitions and discourse around nature-based solutions, we discern a number of assumptions stemming from positivist science that are embedded in the term, and which we find create an inviting space for nature's neoliberalisation processes. We provide empirical analysis of how these assumptions realise in two city-initiated projects in Barcelona, Spain, that have been identified as nature-based solutions: the green corridor of Passeig de Sant Joan and the community garden of Espai Germanetes supported under the municipal Pla Buits scheme. Both projects were born in a neoliberal political climate, but their outcomes in terms of neoliberalism and its contestation were very distinct – not least because of the different forms of governance and socio-natural interaction that these two projects foster. Urban nature can serve elite economic players at the expense of widespread socio-ecological benefits. But it can also serve as a ground for the articulation of demands for open and participatory green spaces that go beyond precarious and controlled stewardship for, or market-mediated interactions with, urban nature. We urge for future research and practice on nature-based solutions to be more critical of the term itself, and to guide its instrumentalisation in urban planning away from neoliberal agendas and towards more emancipatory and just socio-ecological futures.